The Islamization of English literary studies: An introduction - Hasan, Md. Mahmudul (2012)
Literature tells us the story of human life. Like any other literary tradition, English literature concerns human beings, their experiences, sorrows and happiness. This is also very much the case with the religion of Islam whose fundamental message is, as Muslims believe, about what is good and what is bad for human beings, as it is about their wellbeing, meaningful existence and responsibilities on earth as God’s vicegerents (Qur’an, 21:10 & 2:30). So in terms of the central theme, there is a strong commonality between Islam and literature: both primarily concern human life. However, one fundamental difference between them is that, the former is believed to be infallible revelation from God while the latter is subject to human frailty and arrogance, and other shortcomings and limitations. Accordingly, while Muslims generally accept the great bulk of Islamic teachings without any qualms, they are supposed to apply caution to discriminate clearly what is useful for them in both the worlds from what is harmful when they want to transpose the ideas encapsulated in literary works to quotidian life. So it is perhaps important for the Muslim practitioners of English literature to analyze ideas and worldviews expressed in it in the light of the flawless, divine blueprint of Islamic teachings. On the basis of this important theoretical framework, in this paper, I will argue that Islamizing English literature is a viable intellectual endeavor which can provide a direction for scholars of this literary tradition as to how to approach it Islamically.